Growth And Production Of Porang (Amorphophallus Muelleri Blume) Plant Due To Sunlight Intensity And Different Plant Media Formulation - Mita Lestari; Susi Handayani; Edi Susilo; Hesti Pujiwati (UNIVED Press, Dehasen University Bengkulu, 2023)
The porang plant is a tuber-producing plant developed because it can increase farmers' income. Sunlight intensity and the growing environment are essential factors that affect the growth and yield of porang plants. The research aims to get the best shade, planting media formulation, and their interaction for the development and outcome of porang plants. This study applied a randomized group design with the factorial pattern. The first factor is 50%, 70%, and 90% shade. The second factor of planting media formulation is soil or control (100%), soil (50%) + rice husk (16.7%) + coffee husk (16.7%) + manure (16.7%), soil (33.3%) + rice husk (33.3%) + waste (33.3%), soil (66.7%) + coffee husk (16.7%) + rice husk 16.7%). The results showed that 90% shading and planting media formulation of soil (33.3%) + rice husk (33.3%) + manure (33.3%) produced the highest growth (plant height, number of leaves, stem diameter) and porang yield (tuber weight).